CD20×CD3 bispecific antibody achieved significant efficacy in patients with large B-cell lymphoma relapsing after or refractory to CAR-T therapy: a systematic review and meta-analysis - Shen, Jing; Zhang, Jingyi; Zhu, Zhengyu; Ma, Haobo; Li, Xiayan; Zhang, Junpeng; Zhou, Fan; Tian, Hua; Liu, Jinghua (Frontiers in Oncology, 2025)
ObjectiveChimeric antigen receptor T-cell immunotherapy (CAR-T) is a preferred treatment for relapsed or refractory (R/R) large B-cell lymphoma (LBCL). Several trials have evaluated CD20×CD3 bispecific antibodies (BsAbs) as subsequent therapy in R/R LBCL. This study aimed to investigate the efficacy of CD20×CD3 BsAbs (mosunetuzumab, glofitamab, odronextamab, and epcoritamab) in patients with LBCL who experienced relapse or refractory disease following CAR-T therapy.MethodsNine trials involving 350 participants were included, assessing the overall response rate (ORR), complete response (CR), duration of response (DOR), duration of complete response (DoCR), progression-free survival (PFS), and overall survival (OS).ResultsThe specific response rates for different bispecific antibody (BsAb) monotherapies were as follows: Mosunetuzumab: overall response rate (ORR) 40% and complete response (CR) 23%; Glofitamab: ORR 50-76.1% and CR 37-45.7%; Epcoritamab: ORR 54.1% and CR 36%; Odronextamab: ORR 48.3% and CR 31.7%. Upon pooled analysis, the overall ORR was 54.5% (95% CI: 43.1-65.7%) with significant heterogeneity (P=0.013, I²=68.24%), and the CR was 35.6% (95% CI: 29.1-42.2%) with low heterogeneity (P=0.33, I²=13.5%). The specific response rates for different BsAb combinations were as follows: Mosunetuzumab + Pola: ORR 57% and CR 40%; Glofitamab + Pola: ORR 77.8% and CR 44.4%; Epcoritamab + Gemox: ORR 76% and CR 45%; Glofitamab + Gemox: CR 53.8%. Upon pooled analysis, the overall ORR was 70.0% (95% CI: 56.4-82.2%) with no heterogeneity, and the CR was 44.2% (95% CI: 34.5-54.1%) with no heterogeneity. The median duration of follow-up ranged from 13 to 42 months. Data from five trials were available for duration of response (DOR) analysis: 9.7 months, 14.8 months, 19.7 months, not reached, and 2-year rate of 25%, respectively; three trials were available for duration of complete response (DoCR) analysis: one trial reported 22 months, and the others were not reached; six trials were available for median progression-free survival (mPFS) analysis: 3.8 months, 4.8 months, 6.1 months, 9.6 months, 13.7 months, and 31.1 months, respectively; three trials were available for median overall survival (mOS) analysis: 10.2 months, 14.7 months, and not reached, respectively.ConclusionCD20×CD3 bispecific antibodies (BsAbs) exhibit efficacy in relapsed or refractory large B-cell lymphoma (LBCL) patients following CAR-T therapy. To validate these findings and determine the optimal sequencing of BsAbs and CAR-T therapy for R/R LBCL patients, prolonged follow-up periods and further prospective clinical trials are warranted.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024621005.